2014
DOI: 10.1111/1475-6773.12234
|View full text |Cite
|
Sign up to set email alerts
|

A Taxonomy of Accountable Care Organizations for Policy and Practice

Abstract: ACOs can be characterized into three distinct clusters. The taxonomy provides a framework for assessing performance, for targeting technical assistance, and for diagnosing potential antitrust violations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
96
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(99 citation statements)
references
References 33 publications
1
96
0
2
Order By: Relevance
“…Moreover, others have suggested that subspecialists may be most prevalent in larger ACOs and/or ACOs formed from existing integrated delivery systems. 17,18 Our findings generally support this hypothesis with empirical evidence demonstrating that MSSP ACOs with participating urologists are larger organizations, in terms of both beneficiaries and providers, than ACOs not formally involving urologists.…”
Section: Commentsupporting
confidence: 75%
“…Moreover, others have suggested that subspecialists may be most prevalent in larger ACOs and/or ACOs formed from existing integrated delivery systems. 17,18 Our findings generally support this hypothesis with empirical evidence demonstrating that MSSP ACOs with participating urologists are larger organizations, in terms of both beneficiaries and providers, than ACOs not formally involving urologists.…”
Section: Commentsupporting
confidence: 75%
“…8 By holding groups of providers jointly responsible for cost and quality outcomes, the ACO programs attempt to increase coordination of care, reduce unnecessary spending, and improve quality. Beginning in 2012, groups of hospitals, physicians, and other health care providers voluntarily choose to be part of an ACO.…”
Section: Methodsmentioning
confidence: 99%
“…For instance, in the U.S., community-based health and human services are often delivered by networks of independent providers [15]. Additionally, accountable care organisations which can be found in the U.S., but also in countries like Germany, involve inter-organisational collaboration [1617]. The British NHS has experimented with the integration of care through inter-organisational collaboration since the 1990s [8], as have the Nordic countries [18] and the Netherlands [8].…”
Section: Introductionmentioning
confidence: 99%